Functional foods and exercise in breast cancer: epigenetic modulation, chemotherapy tolerance, and fatigue management - Baolei Ma; Haidong Liu (Frontiers in Nutrition)
BackgroundBreast cancer (BC) is the most commonly diagnosed malignancy among women worldwide. There is increasing interest in the role of modifiable lifestyle factors, particularly nutrition and physical activity, in influencing cancer risk, progression, and treatment response.ObjectiveThis review explores how functional foods and exercise can modulate BC through molecular and epigenetic mechanisms and evaluates their potential as adjunctive strategies in prevention and therapy.FindingsFunctional foods, such as those rich in polyphenols, omega-3 fatty acids, vitamins, and probiotics, impact BC biology through DNA methylation, histone modification, and microRNA regulation. Exercise similarly modulates key pathways related to inflammation, immune function, hormone balance, and apoptosis. Combined interventions show synergistic potential in reducing tumor growth, enhancing therapy response, and improving quality of life.ConclusionFunctional foods and exercise represent promising, non-toxic strategies for modulating BC risk and progression via epigenetic and cellular pathways. However, more clinical trials are needed to define optimal combinations and dosages. Future research should focus on precision-based, lifestyle-integrated cancer care approaches.